2009
DOI: 10.1007/s11214-009-9508-7
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Plasmaspheric Wave Research with CLUSTER and IMAGE Observations

Abstract: This paper highlights significant advances in plasmaspheric wave research with CLUSTER and IMAGE observations. This leap forward was made possible thanks to the new observational capabilities of these space missions. On one hand, the multipoint view of the four CLUSTER satellites, a unique capability, has enabled the estimation of wave characteristics impossible to derive from single spacecraft measurements. On the other hand, the IMAGE experiments have enabled to relate large-scale plasmaspheric density struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 154 publications
0
4
0
Order By: Relevance
“…Field‐aligned incidence onto the ionosphere can result from propagation in a field‐aligned density irregularity or duct [ Smith et al , 1960]. Recent results from the Radio Plasma Imager on board the IMAGE spacecraft have shown that the magnetosphere is permeated by irregular density structures that support ducted wave propagation over a wide range of frequencies (see review by Masson et al [2009]). Alternatively, ELF/VLF waves propagating in a nonducted mode, at frequencies below half of the equatorial gyrofrequency, can reach the ionosphere with vertical incidence through a set of specialized ray paths.…”
Section: Diurnal Wave Patternmentioning
confidence: 99%
“…Field‐aligned incidence onto the ionosphere can result from propagation in a field‐aligned density irregularity or duct [ Smith et al , 1960]. Recent results from the Radio Plasma Imager on board the IMAGE spacecraft have shown that the magnetosphere is permeated by irregular density structures that support ducted wave propagation over a wide range of frequencies (see review by Masson et al [2009]). Alternatively, ELF/VLF waves propagating in a nonducted mode, at frequencies below half of the equatorial gyrofrequency, can reach the ionosphere with vertical incidence through a set of specialized ray paths.…”
Section: Diurnal Wave Patternmentioning
confidence: 99%
“…Those energetic and anisotropic ring current protons are considered to provide the major source of free energy driving this instability and causing the amplification of EMIC waves [ Anderson et al , 1992a; Erlandson and Ukhorskiy , 2001; Engebretson et al , 2007]. Since the instability threshold is so low that EMIC waves are easily generated in the presence of cold dense ions [ Gary et al , 1995], strong enhancements of the EMIC wave power occur at the plasmapause [ Anderson et al , 1992a; Fraser and Nguyen , 2001; Masson et al , 2009]. In fact, since cold He + ions have a strong influence on the proton cyclotron electromagnetic instability [ Gomberoff and Cuperman , 1982; Kozyra et al , 1984], most observed EMIC waves in the frequency range of Pc1‐2 have spectra whose characteristic frequencies are organized in the vicinity of the He + gyrofrequency at the equatorial plane [ Young et al , 1981; Sakaguchi et al , 2008].…”
Section: Introductionmentioning
confidence: 99%
“…The Earth's plasmasphere is an important plasma region of the terrestrial magnetosphere‐ionosphere system, playing a significant role in the dynamics of the magnetosphere‐ionosphere coupling during quiet and active periods alike (Darrouzet et al., 2009; Goldstein et al., 2004; Kotova, 2007; Lemaire & Gringauz, 1998; Masson et al., 2009; Moldwin et al., 2016; Reinisch et al., 2009; Yizengaw & Moldwin, 2005). During magnetic storms the mass loading and unloading of the plasmasphere is an integral part of the storm process, with widespread implications for a variety of processes in the magnetosphere and/or ionosphere (Sheeley et al., 2001; Yizengaw et al., 2005a).…”
Section: Introductionmentioning
confidence: 99%